PENGARUH KETAATAN ATURAN AKUNTANSI, ASIMETRI INFORMASI, KEADILAN DISTRIBUTIF DAN KEEFEKTIFAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Organisasi Perangkat Daerah di Kabupaten Rokan Hulu - Isna Kurniati; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research are to analyze compliance to accounting rules, information asymmetri, distributive justice and the effectiveness of internal control to the tendency accounting fraud with unethical behavior as intervening variable. This research was conducted at 29 regional device organization in Rokan Hulu with 112 respondents. The data were analyzed by using PLS (Partial Least Square) analysis technique, while the method of determining the sample is by using purposive sampling method. The result show that compliance of accounting rules has no effect on the tendency of accounting fraud. Nonetheless, information asymmetry, distributive jutice and the effectiveness of internal control have direct influence toward tendency of accounting fraud. The influence of compliance to accounting rules, information asymmetry and distributive justice was significantly affecting the unethical behavior, but the effectiveness of internal control does not have influence toward unethical behavior. The influence of compliance to accounting rules, information asymmetry and distributive justice was significantly affecting the tendency of accounting fraud through unethical behavior. But, the effectiveness of internal control does not have significantly affecting to tendency of accounting fraud through unethical behavior.Keywords : Adherence to accounting rules, Information Asymmetry, Distributive Justice, Effectiveness of Internal Control, Tendency Accounting Fraud and Unethical Behavior.